Konsep Pendidik Perspektif Az-Zarnuji - Moh. Faizin; Muhammad Fikri Haikal Pratama; Reza Nabila (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to analyze and describe the effectiveness and contribution of the This article discusses in depth the concept of educators according to Az-Zarnuji's perspective in his book